Syrian Refugees’ Participation in Language Classes: Motivators and Barriers - Ives, Nicole; Oda, Anna; Bridekirk, Jonathan; Hynie, Michaela; McGrath, Susan; Mohammad, Rana; Awwad, Mona; Sherrell, Kathy; Khalaf, Mahi; Diaz, Marcela (Refuge: Canada’s Journal on Refugees, 2022)
Resettlement country language literacy facilitates integration and counteracts social and economic marginalization. Thus, access to language learning is a social justice issue. Resettled refugees in Canada are eligible for free English/French language training. Between 2015-2017, Canada resettled 47,735 Syrian refugees. We explored predictors of language class participation for Syrian refugees, examining data from 1915 adult Syrian refugees in government-funded language classes in British Columbia, Ontario, and Quebec. Findings suggest access to language programs are shaped by provincial policies. Factors hindering participation varied by province and included gender, physical/mental health, education, English/French literacy, and employment. Practice and policy recommendations are discussed.